Does neuroticism make you old? Prospective associations between neuroticism and leukocyte telomere length. Issue 4 (9th July 2013) - van Ockenburg, S. L.; de Jonge, P.; van der Harst, P.; Ormel, J.; Rosmalen, J. G. M.
Abstract : Background: Telomere attrition, causing accelerated aging, might be one of the mechanisms through which neuroticism leads to somatic disease and increased all-cause mortality. In the current study we investigated whether neuroticism is prospectively associated with shorter telomere length (TL), a biological marker of aging. Method: Participants were 3432 adults (mean age 52.9 years, range 32–79). Data were collected at baseline (T1) and at two follow-up visits after 4 years (T2) and 6 years (T3). Neuroticism was assessed using the 12-item neuroticism scale of the Revised Eysenck Personality Questionnaire (EPQ-R) at T2 and T3. TL was measured by a monochrome multiplex quantitative polymerase chain reaction (PCR) assay at T1, T2 and T3. A linear mixed model was used to assess whether neuroticism could predict TL prospectively after adjusting for age, sex, body mass index (BMI), frequency of sports, smoking status, presence of chronic diseases and level of education. Results: Neuroticism was a significant negative predictor of TL at follow-up ( B  = −0.004, p  = 0.044) after adjusting for sex, age, baseline TL and various biological and lifestyle factors. Conclusions: High neuroticism is significantly and prospectively associated with telomere attrition independent of lifestyle and other risk factors.